Preoperative MRI for oral tongue squamous cell carcinoma: timing and correlation to histopathology. Issue 3 (March 2023) - Rozendorn, N.; Greenberg, G.; Madgar, O.; Gluck, I.; Vered, M.; Alon, E.; Dobriyan, A.
Abstract: Magnetic resonance imaging (MRI) is an integral part of the evaluation of local and regional disease in tongue squamous cell carcinoma prior to surgery. The aim of this study was to evaluate the accuracy of MRI in assessing tumour dimensions, as well as the impact of the time-lag from diagnostic biopsy on the accuracy of MRI. The medical records of 64 patients with tongue carcinoma were reviewed retrospectively. Tumour maximum diameter and tumour depth of invasion were compared between pathology and MRI (T1- and T2-weighted). MRI-derived maximum tumour diameter and depth of invasion correlated strongly with histopathology: T1-weighted ( r  = 0.700 and r  = 0.813, respectively) and T2-weighted ( r  = 0.734 and r  = 0.834, respectively). A significant correlation was found between measurements on T1 and T2 MRI for both parameters ( P  = 0.955 and P  = 0.984, respectively). The accuracy rate of MRI for T-staging of early tumours was low: 10% for T1 tumours; 39.3% for T2 tumours. A time-lag of less than 2 weeks between the diagnostic biopsy and MRI adversely affected the correlation of tumour dimensions. MRI is a reliable tool for evaluating tongue carcinoma; however, it overestimates early tumours. A 2-week delay after diagnostic biopsy is desired before completing an MRI. Alternatively, if logistics allow, a pre-biopsy MRI is preferred, especially for T1–T2 tumours.